El emigrante ecuatoriano, un desarraigado permanente (Estudios) - Salazar Estrada, Yovany (2015)
This essay illustrates and analyzes three of the major issues that affect and cause suffering to the Ecuadorian immigrant and his immediate family environment in the host country and in the region: the uprooting and its consequences, continuous reflections on the journey; and the dream of returning to Ecuador and disappointments that come when this postponed longing comes true, in accordance with what one imagines, recreates, describes, and hints in the narrative of the novels that represent the sociological phenomenon of the international migration of Ecuadorians towards more developed national states in the Northern Hemisphere, preferably the United States and Spain.